The clinical and morphological aspects of aetiology and pathogenesis of sacrococcygeal pilonidal cysts - Ye. V. Tsema; Yu. V. Dibrova (Zaporozhye State Medical University, 2013)
Introduction. The occurrence of pilonidal cysts in Ukrainian population is up to 50 cases per 100.000. Nevertheless, the cause and the pathogenesis of pilonidal cyst to date remain unclear. There are two opposite views on the etiology of the pilonidal disease stating it has congenital or acquired origin. Authors suggest the definite answer should be based primarily on the results of the morphologic evaluation of pilonidal cyst tissue. Aim: To explore the morphological features of sacrococcygeal pilonidal cysts by means of histological evaluation of cyst tissue after the wide local excision of the cyst. Methods: We performed complex morphological evaluation of cyst tissue obtained after the wide local excision of pilonidal cyst to find out particulars of sacrococcygeal pilonidal cyst histological structure. In total, we evaluated 42 surgical specimens obtained after the wide local excision of pilonidal cyst complicated by the secondary sinus tract formation. The microscopy was performed with the light microscope Leica DM LS2 (ocular lens: х10, objective lens х10 or х20, camera's optical zoom х4). Histological samples were stained with hematoxylin and eosin using the standard method. Discussion. The absence of own epithelial elements in the pilonidal cysts and the secondary sinus tracts have been demonstrated. Hypertrophic growth of skin or hair follicle epithelium was evident in some specimens. Such changes seen in the deep layers of skin on the border with adipose tissue were similar to epidermal polyps. Results. There are some morphological features suggesting the acquired origin of the pilonidal disease as follows: - Hair found in the pilonidal cyst's tissue is not associated with hair follicles, and occurs as loose shafts with atrophied hair bulb, and their exogenous transdermal penetration is evident. - Pilonidal cyst doesn't have own epithelium, and the epithelial fragments that occur are the fragments of disorganized hair follicles. - In the pilonidal cyst's tissues immunopathological cell reactions of foreign body rejection are evident. Disorganization and lysis of hair shafts, vessel hyalinosis, fibrinoid degeneration and lymphoid cells infiltration are critical components of pilonidal cysts morphogenesis. - The important role in the consistent development of pathogenetic mechanisms of sinus ducts formation in sacrococcygeal pilonidal disease is played by common pathological mechanisms of tubular sinus ducts formation with hypertrophic skin epithelium growth in the external sinus tract area and on the fundus of enlarged hair follicle with 'epithelial polyp' formation. Conclusion: 1. Pilonidal disease has an acquired origin and develops when the loose hair shafts penetrate into skin through the destroyed hair follicles in the intergluteal cleft. 2. Pilonidal cyst formation is associated with hyperergic cell immunopathological delayed-type reaction that develops in soft tissues of sacrococcygeal area. 3. The application of special methods of immunohistochemistry and morphology is necessary for more comprehensive evaluation of histogenetic mechanisms of sacrococcygeal pilonidal cyst formation.